ANALISIS AKUISISI MODAL DAN STRATEGI PEMBAYARAN KEMBALI PADA STARTUP DI INDONESIA: STUDI KASUS GOTO GOJEK TOKOPEDIA TBK - Najwa Adilla Taira Eko; Ahmad Rifaldi S; Jilan Fadhillah; Ratuliu; Fina Ruzika Zaimar (STKIP Subang, 2025)
This study analyzes capital acquisition and repayment strategies at PT GoTo Gojek Tokopedia Tbk, one of the largest technology companies in Indonesia. The study uses a qualitative approach through a systematic literature review combined with content analysis of financial reports, IPO prospectuses, official publications, and previous studies from 2020 to 2025. The analysis shows that GoTo's capital acquisition process through strategic investor funding, venture capital, and IPO has succeeded in increasing assets and equity without putting direct pressure on cash flow. However, this increase in capital has not resulted in a significant improvement in profitability due to high operating costs, post-merger integration expenses, and a high proportion of short-term debt. Efficiency analysis shows an increase in operational efficiency, but the company's capital structure still faces liquidity pressures and short-term financial risks. The findings confirm that successful business consolidation through mergers does not automatically strengthen financial performance, requiring a more targeted repayment strategy through debt restructuring, asset optimization, and cost efficiency. This research contributes to the development of capital structure studies in technology companies and provides practical recommendations for digital startups in formulating sustainable funding strategies.